Statistical Analysis of Factors Influencing the Liquid and Plastic Limits of Fine-Grained Soil Mixtures - Verma G.; Kumar B. (My University, 2025)
Atterberg limits comprise of liquid and plastic limits which are widely used for the identification and classification of fine-grained soil. For the last five-six decades, researchers attempted to correlate these limits with various engineering properties like permeability, compaction parameters and shear strength. Naturally, available soil comprises of clay, silt and sand fractions which make it complex to distinguish their effect on both liquid and plastic limits. This study is to investigate the factors affecting the liquid limit, through fall-cone penetrometer method, and plastic limits, using the thread-rolling method, of clay admixed artificially with limestone dust (LSD) and fine sand (FS) severally as well as collectively. Based on the statistical analysis of 44 laboratory test results, it has been found that these limits are primarily controlled by the clay content, marginally by the particle size and least by the fractions of silt- and sand-sized particles. Moreover, Pearson’s correlation analysis reveals that liquid and plastic limits of fine-grained soil mixtures are in perfect positively associated with % bentonite, moderate negatively with % LSD and weak negatively with % FS. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.